E-Commerce Road Map as a Legal Protection for Consumers in The Digital Economic Era - Rizka Rizka (Universitas Muhammadiyah Sidoarjo, 2019)
Digitalization of the economic field to welcome the era of industrial revolution 4.0 needs to be addressed intelligently so it is not harm the consumers and business actors through the transformation of consumer protection instruments into a more contemporary way. Currently, Indonesia has about 93.4 million Internet users and approximately 71 million users of smart phones which makes the internet and of course online transactions, as part of a lifestyle that is reflected through shopping behavior. The task of the State is to bring legal protection to consumers. Based on the consideration of actuality and urgency, to create the necessary level of certainty in business transactions and protect the consumer rights of e-commerce transactions the Government finally issued Presidential Regulation No. 74 of 2017. This regulation regulates the Electronic Road Based Electronic System Road Map (road map e-commerce). The Policy Package is intended to make Indonesia the largest digital economy in Southeast Asia by 2020. Legal umbrella is required in the form of law so that the state can provide a simultaneous and comprehensive legal protection of consumer rights in e-commerce transactions in the era of digital economy.